Pluralism, the Lucas critique, and the integration of macro and micro - Peter Skott (University of Massachusetts, Department of Economics, 2012)
Mainstream macroeconomics has pursued 'micro founded' models based on the explicit optimization by representative agents. The result has been a long and wasteful detour. But elements of the Lucas critique are relevant, also for heterodox economists. Challenging common heterodox views on microeconomics and formalization, this paper argues that (i) economic models should not be based purely on empirically observed regularities, (ii) heterodox economists must be able to tell an integrated story about goal-oriented micro behavior in a specific macro environment, and (iii) relatively simple analytical models have an essential role to play.
Keywords: E1; B5; 330; micro foundations; pluralism; old Keynesian theory; Kaleckian investment function